Abelardo Gamarra “El Tunante” and the narrator serrano in costumbrist articles in “Rasgos de Pluma” (1875-1877) - Torres Espinoza, Jannet (2018)
Abelardo Gamarra presented in his costumbrist articles a costumbrist narrator with distinctive serrano features of an outsider in Lima. Different aspects of his biography as a writer and the context of migrations from the Andean countrysideto Lima in the middle of the XIX are an important aspect of this article. I analyze three related motifs in his articles: the meaning of the pseudonym “El Tunante”, thecriticisim to Lima and the narrator’s nostalgia for the life in the Andes. For the present study I have selected four articles published in his column “Rasgos de Pluma” in the Peruvian newspaper El Nacional between 1875 and 1877.